UPAYA PENANGGULANGAN PENYEBARAN PAHAM RADIKAL TERORISME MELALUI MEDIA SOSIAL: PLATFORM FACEBOOK - Fintiara Mey Arianti; Farhana (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
This study aims to analyze the efforts to counter the spread of radical terrorist ideologies through social media, focusing specifically on Facebook as a digital platform often exploited by extremist groups for propaganda dissemination, recruitment, and network building. The research employs a normative juridical approach supported by qualitative descriptive methods, utilizing literature reviews, legal documents, and official reports from institutions such as Indonesia’s National Counterterrorism Agency (BNPT). The findings indicate that although regulations such as Law No. 5 of 2018 on the Eradication of Terrorism Crimes are in place, the enforcement of legal norms in the digital sphere remains insufficient. The absence of binding obligations for social media platforms to monitor and remove radical content has resulted in reactive rather than preventive responses. Current deterrence measures are inadequate in curbing the spread of radical ideologies. Therefore, a more comprehensive approach is required, involving legal reform, digital literacy campaigns, cooperation with digital platforms, and active participation from religious organizations in deradicalization efforts. This research recommends a multidimensional strategy that combines law enforcement with preventive education and ideological resilience-building within communities.